STUDY AND RESEARCH ON CLEANING PROCEDURES OF ANAEROBIC DIGESTION PRODUCTS - Heviánková, Silvie; Kyncl, Miroslav; Kodymová, Jana (GeoScience Engineering, 2014)
This paper focuses on increasing quantities of digestate, a final product of anaerobic digestion, in biogas stations being built as alternative sources of energy. The potential use of digestate is limited due to its rather specific physical properties. This paper presents current approaches to digestate and digestate management. The objective is to compare the properties of digestate and the products of its separation via centrifuging, i.e. the liquid phase known as digestate liquor, and the solid phase referred to as digestate fibre. Its focus is mainly laid on techniques for dewatering digestate in low-solid anaerobic processes only, which have been tested for the effectiveness of the basic physical and chemical methods including their combinations. The measured results show that the use of coagulants and flocculants for this purpose would be very problematic in practice with regard to their high consumption as well as the need to input other elements into the process.